ConStruct 1.0: An R Script to distinguish between substructure and consanguinity within a population using multilocus microsatellite data. Issue 1 (31st December 2016) - Overall, Andrew D.J.
Abstract : ConStruct.1.r is an R Script that estimates the relative contributions of consanguinity and population substructure to excess homozygosity. ConStruct.1.r also offers the option of simulating data with a given F S T and magnitude of consanguinity, incorporating a user-specified number of loci, number of alleles and population size. The method seems robust when population sizes are above 200 and individuals are genotyped at greater than 10 loci.